Advanced introduction to international human rights law - Shelton, Dinah L. (Edward Elgar Pub, 2014)
' Professor Shelton blends basic, essential information on human rights with just the right amount of material on the larger frameworks - ethical, historical, institutional and political - that are critical to any dynamic understanding of the ways in which the ideas and practices of human rights have been shaped and take concrete form today. The result is a very welcome and greatly needed book, which will be extremely useful as both a reference text and a teaching tool. ' - Paolo Carozza, University of Notre Dame, US ' This is the first comprehensive English language textbook on international human rights law. Written by a leading scholar in the field, this book provides an insightful analysis of the normative principles comprising this ever-expanding subject. Equally valuable is the extensive overview of the practice of universal and regional judicial and quasi-judicial institutions that apply and help create contemporary international human rights law. Scholars and practitioners alike will find this book to be an indispensable resource in their work. ' - Judge Thomas Buergenthal, George Washington University Law School, US Elgar Advanced Introductions are stimulating and thoughtful introductions to major fields in the social sciences and law, expertly written by the world's leading scholars. In this landmark text, Dinah L. Shelton offers an insightful overview of the current state of international human rights law: its norms, institutions and procedures, both global and regional. Designed to be accessible, yet rigorously executed, the Advanced Introduction to International Human Rights Law provides a concise and lucid account of this field of international law, from a leading authority on the subject. Providing an invaluable entry point to this complex area of the law, as well as an insightful reference for seasoned experts, the book will prove a useful resource for professors and practitioners of international law. It will also serve as a stimulating introductory text for both undergraduate and postgraduate courses on human rights. Key features include: - Comprehensive coverage presented in an accessible style, structured into short, focused chapters - A rounded, interdisciplinary approach which places the law in context - Exploration of both practical and theoretical aspects - Balanced coverage with attention to both regional and global organizations, as well as probing current challenges - Written with the authority of an insider. Contents : 1. Concepts and Foundations 2. Historical Overview 3. International Institutions 4. The Law of Human Rights 5. The Rights Guaranteed 6. Obligations 7. Compliance and Monitoring Mechanisms 8. Complaint Procedures 9. Enforcement 10. Stock-taking Index.